Algorithms of work the module "Accounts Payable" in the ERP-system Axapta 3.0; Korus 2005 - Tulmenkov V. N.; Zamyatina O. M. Oksana Mikhailovna; Sanochkina N. G.; Dmitrieva E. A. Elena Anatolievna; Tsapko G. P. Gennady Pavlovich; Yakupov V. A. (2005, 2005)
Title screen